2020
DOI: 10.1002/cam4.3014
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines and chemokine receptors: A new strategy for breast cancer therapy

Abstract: Chemokines and chemokine receptors not only participate in the development of tissue differentiation, hematopoiesis, inflammation, and immune regulation but also play an important role in the process of tumor development. The role of chemokines and chemokine receptors in tumors has been emphasized in recent years. More and more studies have shown that chemokines and chemokine receptors are closely related to the occurrence, angiogenesis, metastasis, drug resistance, and immunity of breast cancer. Here, we revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 101 publications
(152 reference statements)
0
54
0
Order By: Relevance
“…The primary role of chemokines is to participate in leukocyte development, differentiation, and migration. However, chemokines are also involved in angiogenesis, wound healing, inflammatory diseases, and progression of malignancies, such as adult T-cell leukemia and many solid tumors [ 6 , 7 , 8 , 9 , 10 ]. Although chemokines exert antitumor effects, including induction of cytotoxic T cells into tumor tissues, they have also been known to assist cells that suppress tumor immunity, such as tumor-associated macrophages (TAM), myeloid-derived immune suppressor cells (MDSC), and regulatory T cells (Treg) [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The primary role of chemokines is to participate in leukocyte development, differentiation, and migration. However, chemokines are also involved in angiogenesis, wound healing, inflammatory diseases, and progression of malignancies, such as adult T-cell leukemia and many solid tumors [ 6 , 7 , 8 , 9 , 10 ]. Although chemokines exert antitumor effects, including induction of cytotoxic T cells into tumor tissues, they have also been known to assist cells that suppress tumor immunity, such as tumor-associated macrophages (TAM), myeloid-derived immune suppressor cells (MDSC), and regulatory T cells (Treg) [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chemokines and chemokine receptors play crucial roles in the progression of breast cancer, including its occurrence, immune responses, angiogenesis, metastasis, and drug resistance [ 2 ]. Our study aimed to evaluate the roles of XCL1 and its specific receptor XCR1 in MDA-MB-231 cell migration as well as to identify the underlying signaling pathway mediating this process.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the effectiveness of current pharmacological therapies for breast cancer is generally limited. Thus, developing new strategies to effectively reduce breast cancer progression and metastasis is crucial [ 2 ]. Novel immunotherapies targeting the chemokine system, including chemokines and their receptors, are promising strategies for breast cancer therapy [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the good tumor marker should be highly sensitive, easy to measure, and reproducible. A large number of observations suggested that intrinsic properties of the tumor cells, as well as macro-environmental factors, with a direct interaction of the tumor cells with chemokines and their receptors, are involved in breast tumorigenesis and tumor progression (Liu et al, 2020;Suman et al, 2016). Chemokines and chemokine receptors play a crucial role in these processes since they participate in the trafficking of cells into and out of the tumor microenvironment (Ali & Lazennec, 2007).…”
Section: Introductionmentioning
confidence: 99%